SÃ”BRE UM NEMATÃ“DEO DO GÃŠNERO Pratylenchus, PARASITO DAS RAÃZES DE Allium cepa - Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2016)
SÃ”BRE UM NEMATÃ“DEO DO GÃŠNERO Pratylenchus, PARASITO DAS RAÃZES DE Allium cepa